Surveillance, Prevention, Evolution and Control of Emerging Viruses: A 2022 Editorial Update - Maite Freitas Silva Vaslin; Luciana de Barros Arruda; Fabricio Souza Campos (Viruses, 2023)
The Special Issue “Emerging Viruses: Surveillance, Prevention, Evolution and Control” has been published annually by Viruses, since 2019, highlighting the increasing effort of the scientific community for the surveillance and further research of new emerging or re-emerging viruses [...]